KLAUSUL BAKU LAZADA YANG MERUGIKAN KONSUMEN MENURUT PASAL 18 AYAT 2 UNDANG - UNDANG PERLINDUNGAN KONSUMEN (ANALISIS PUTUSAN NOMOR 588/PDT.G/2020/PN.JKT.BRT - Muteguh, (2023)
Consumer protection is a consequence and part of technological and industrial advances. These technological and industrial advances have in fact strengthened the differences between the lifestyle of traditional society and today's modern society. Traditional society produces consumer goods in a simple manner, and the relationship between consumers and traditional communities is still relatively simple, where consumers and producers can meet face to face. Meanwhile, modern society produces consumer goods in bulk, thereby creating mass consumers (mass consumer consumption). Finally, the relationship between consumers and producers becomes complicated, where consumers do not know who the producers are, and vice versa, even these producers are in other countries and sometimes this makes it necessary to have a standard agreement. Consumer protection in Indonesia is regulated in Law No. 8 of 1999, in the article there are standard clause rules where these clauses are permissible as long as they do not conflict with the law and harm consumers. The standard clause/standard agreement itself is part of an agreement so that the arrangement for this matter must be based on the rules contained in the Civil Code (KUHPerdata) in CHAPTER III Concerning Contracts in general. In addition, because the Standard Clause is in fact a lot detrimental to the consumer and also the Standard Clause shows that there is an imbalance in the position between consumers and producers with the impression that producers are forcing these clauses on consumers, the regulation is also contained in Law No. 9 of 1999 concerning Consumer Protection ( UUPK). In the event that Lazada's standard clause is detrimental to consumers, in which clause the privacy policy is not very transparent and the dispute resolution is also not explained clearly, so that in lawsuit number 588/Pdt.g/2020/Pn.Jkt.Brt, consumers feel disadvantaged because their lawsuit is rejected and not in accordance with the privacy policy by Lazada Indonesia which has been regulated in the standard clause. Based on the results of the author's research, there are things that are detrimental to consumers, including the Lazada standard clause is too hidden so that its location is not easily understood or read by consumers who will register, Lazada's standard clause is detrimental to consumers because with small nominal disputes it requires consumers to make settlements in arbitration which with a small nominal is impossible, so it is clear that Lazada's standard clause is very detrimental to consumers.